Pre-conception blood pressure and evidence of placental malperfusion - Jacqueline Atlass; Marie Menke; W. Tony Parks; Janet M. Catov (BMC, 2020)
Abstract Background Evidence of placental maternal vascular malperfusion is associated with significant perinatal outcomes such as preeclampsia, intrauterine growth restriction and preterm birth. Elevations in pre-pregnancy blood pressure increase the risk for poor perinatal outcomes; however, the evidence linking pre-pregnancy blood pressure and placental malperfusion is sparse. Materials and methods We conducted a retrospective case-control study of women with singleton gestations with placental evaluations who delivered at Magee-Womens Hospital in 2012. Charts from 100 deliveries with placental malperfusion lesions (vasculopathy, advanced villous maturation, infarct, or fibrin deposition) and 102 deliveries without placental malperfusion were randomly selected for screening. Blood pressure, demographic, and clinical data were abstracted from pre-pregnancy electronic medical records and compared between women with and without subsequent placental malperfusion lesions. Results Overall, 48% of women had pre-pregnancy records, and these were similarly available for women with and without placental malperfusion. Women with placental malperfusion demonstrated a reduction in their pre- to early pregnancy decrease in diastolic blood pressure (DBP). Adjusted for race, pre-pregnancy BMI, age, pre-conception interval, and gestational age at the first prenatal visit, the difference in pre- to early pregnancy DBP was significantly less in women with placental malperfusion compared to those without this pathologic finding (− 1.35 mmHg drop vs − 5.6mmg, p < 0.05). Conclusion A blunted early gestation drop in DBP may be a risk factor for placental malperfusion, perhaps related to early pregnancy vascular maladaptation. The ability of the electronic medical record to provide pre-pregnancy data serves as an underutilized approach to study pre-pregnancy health.